ScrumZero: AI Powered Agile Workflow Optimizer - Desai, Yuvraj (International journal for research in applied science and engineering technology, 2025)
Scrum-Zero is an AI-powered web application that automates the work of the Scrum Master of Agile teams, which is the subject of our paper. Scrum-Zero is a system built with FastAPI on the backend and React-like Java script frontend powered by Google generative AI engine, Gemini-2.0, with daily stand up, sprint discipline and real time to-do prioritization and bottleneck solving built in. The system maintains tasks between meetings in SQLite and makes RESTful calls on each stage of the process of task life-cycles. The AI summary module categorizes team task updates into Completed, In-Progress and To-Do and provides an organized and actionable stand-up report. Using a controlled study of 30 practitioners, we estimate the summary latency of Scrum-Zero, compare it to the accuracy of reports collected by humans [1], and learn about user satisfaction. The findings show that it takes less time to meet (average reduction of 40 percent), 85 percent of the claims to be in agreement with human summaries and that it can be used as an AI facilitator of an Agile workflow [2]. We talk about design and architecture, knowledge of the difficulties in AI implementation, and ways to expand on it to increase capacity and multimodality. Index Terms- AI Scrum Master, Agile Automation, Generative AI, Fast API, Scrum-Zero.